The Proceedings of the 2018 Asia-Pacific International Symposium on Aerospace Technology (APISAT 2018) - Zhang, Xinguo; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book is a compilation of peer-reviewed papers from the 2018 Asia-Pacific International Symposium on Aerospace Technology (APISAT 2018). The symposium is a common endeavour between the four national aerospace societies in China, Australia, Korea and Japan, namely, the Chinese Society of Aeronautics and Astronautics (CSAA), Royal Aeronautical Society Australian Division (RAeS Australian Division), the Korean Society for Aeronautical and Space Sciences (KSAS) and the Japan Society for Aeronautical and Space Sciences (JSASS). APISAT is an annual event initiated in 2009 to provide an opportunity for researchers and engineers from Asia-Pacific countries to discuss current and future advanced topics in aeronautical and space engineering.
Aerodynamics and Design -- Structures and Materials -- Dynamics/Control/Avionics -- Combustion and Propulsion.
Keywords: Aerospace engineering; Astronautics; Continuum mechanics; Mechanics, Applied; Control engineering; Aerospace Technology and Astronautics; Continuum Mechanics; Engineering Mechanics; Control and Systems Theory